Impulsivity in body-focused repetitive behavior disorders: Disparate clinical associations between three distinct measures. (2nd January 2016) - Leppink, Eric W.; Redden, Sarah A.; Grant, Jon E.
Abstract: Objective: Research on trichotillomania (TTM) and excoriation (skin-picking) disorder (SPD) has suggested that impulsivity may be an important cognitive underpinning of the behavior, but many studies have produced mixed results. This analysis assessed impulsivity in TTM and SPD using three measures: the Barratt Impulsiveness Scale (BIS), the Eysenck Impulsiveness Questionnaire (EIQ), and the Stop-Signal Task (SST). Methods : Two hundred and eighty three subjects with TTM or SPD completed measurement of impulsivity as a part of participation in several research studies. Subjects scoring one standard deviation above or below measure means were included in the analysis for that scale (SST: N  = 45; EIQ: N  = 32; BIS: N  = 34). High and low impulsive groups were compared within measures on demographic, clinical, and behavioral variables. Results : Results differed by group, with domains of the BIS showing associations with clinical severity, quality of life, and anxiety, and the SST showing several differences, but not clinical severity. The EIQ domains showed no significant differences. No groups differed demographically. Conclusions : These results suggest that the EIQ, BIS, and SST assess distinct characteristics. Notably, only the attentional domain from the BIS predicted higher severity scores. Future research needs to clarify the ideal utility for these scales as they relate to TTM and SPD. Key points: The BIS, EIQ, and SST domains are associated with distinct clinical differences between high and low impulsivity groups. Only the subjects in the high attentional impulsivity domain of the BIS showed significantly elevated symptom severity. The high and low impulsivity groups within the EIQ domains did not show any significant differences. These disparate associations may indicate the need for better subtyping of impulsivity, as different measures of specific domains appear to show associations with distinct features.